Relative impact of acute heart failure and acute kidney injury on short- and long-term prognosis of patients with STEMI treated with primary PCI. (14th October 2021) - Milasinovic, D; Mladenovic, D J; Jelic, D; Zobenica, V; Zaharijev, S; Vratonjic, J; Isailovic, N; Radomirovic, M; Pavlovic, A; Vukcevic, V; Asanin, M; Stankovic, G
Abstract: Background: Although both acute heart failure (AHF) and acute kidney injury (AKI) have been separately recognized as contributors to an increased mortality risk in patients with ST-segment elevation myocardial infarction (STEMI), their relative importance has not been extensively studied. Purpose: Our aim was to investigate the relative impact of AHF and AKI on 30-day and 5-year mortality following primary PCI for STEMI. Methods: 8 054 patients referred to primary PCI during the years 2009–2019, and with the available repeated creatinine measurements, were analyzed. AKI was defined as ≥25% relative or ≥0.5 mg/dl absolute rise in creatinine from baseline, within 72 hours of intervention. Acute heart failure was defined as Killip class ≥2 on admission to hospital. Cox regression model was used to assess the effect of the interaction of AHF and AKI on mortality. Median follow-up was 5 years. Results: The incidence of AKI was 9.9% (n=805) and of AHF 12.3% (n=1050). Concurrence of AHF and AKI was noted in 1.7% of the included patients (n=315). The combined presence of AHF and AKI significantly increased mortality both at 30 days (30.7%) and at 5 years (73.3%), as compared with AKI alone (8.2% at 30 days and 32.3% at 5 years) and AHF alone (13.0% and 53.0%). When adjusted for other significant predictors, such as age, prior stroke, hyperlipidemia, atrial fibrillation, ejection fraction, final TIMI flow in the culprit artery, the use of intra-aortic balloon pump and multivessel disease, both AKI and AHF were independently associated with mortality. The adjusted relative impact of AKI on mortality was stronger than that of AHF at 30 days (adjusted HR 3.5 and 2.2, respectively), whereas it was comparable at 5 years (adjusted HR 1.3 and 1.4, respectively). Furthermore, the combined presence of AHF on admission and the post-primary PCI development of AKI was associated with the highest magnitude of risk at both 30 days (HR 5.0, CI95% 3.0–8.3, p<0.001) and 5 years (HR 2.4, CI95% 1.83–3.16, p<0.001). Conclusion: Acute kidney injury following primary PCI for STEMI was associated with a higher adjusted risk of short-term mortality when compared with acute heart failure, whereas their relative impact was comparable in the long-term. FUNDunding Acknowledgement: Type of funding sources: None.